Freud on Madison Avenue : motivation research and subliminal advertising in America - Samuel, Lawrence R. (EBL-Schweitzer, 2010)
Freud on Madison Avenue tells the story of how and why mid-twentieth-century advertisers adopted Freudian psychology to sell products. This study follows the careers of Paul Lazarsfeld, Herta Herzog, James Vicary, Alfred Politz, Pierre Martineau, Edward Bernays, and the father of motivational research, Ernest Dichter.